Recent Advances in Regenerative Tissue Fabrication: Tools, Materials, and Microenvironment in Hierarchical Aspects. Issue 5 (22nd March 2021) - Ratri, Monica Cahyaning; Brilian, Albertus Ivan; Setiawati, Agustina; Nguyen, Huong Thanh; Soum, Veasna; Shin, Kwanwoo
Abstract : As part of regenerative medicine, artificial, hierarchical tissue engineering is a favorable approach to satisfy the needs of patients for new tissues and organs to replace those with defects caused by age, disease, or trauma or to correct congenital disabilities. However, the application of tissue engineering faces critical issues, such as the biocompatibility of the fabricated tissues and organs, the scaffolding, the complex biomechanical processes within cells, and the regulation of cell biology. Although fabrication strategies, including the traditional bioprinting, photolithography, and organ‐on‐a‐chip methods, as well as combinations of fabrication processes, face many challenges, they are methods that can be used in hierarchical tissue engineering. The strategic approach to synthetic, hierarchical tissue engineering is to use a combination of several technologies incorporating material science, cell biology, additive manufacturing (AM), on‐a‐chip strategies, and biomechanics. Herein, in a review, the current materials and biofabrication strategies of various artificial hierarchical tissues are discussed based on the level of tissue complexity from nano to macrosize and the adaptive interactions between cells and the scaffolding surrounding the incorporated cells. Abstract : Tissues and organs of living organisms are highly organized and structured, following a hierarchy. For the engineering of tissues for the purposes of regenerative medicine, therefore, fabrication is an essential part of constructing a natural hierarchical structure. This review introduces the biological requirements and the recent technical strategies to implement them hierarchically.